Market Entry Into South Africa: Plans And Strategies For Malaysian International Trading Coproration (MITCO) - Khalid Rashid, Syed Abid (2003)
This paper is designed to serve as a small guideline on business expansion for business leaders. This paper will also give special attention to marketing in South Africa and its benefits.